Design and construction of a rotor test bench for testing and evaluating sensors. (2020) - Holl, Helmut J.; Pfaffenbauer, Martin
Abstract: A rotor test bench is developed to study and test a new sensor device for defined operation conditions. The specification of the operation conditions is given and the rotor test bench has to be designed so that the effort for the performance of the test procedure is as small as possible and efficient. The tested sensor is attached at a defined position on the rotor similar as in the real design in the motor. As high rotation speeds are used the applied balancing procedure has to be performed in some steps at different rotation speeds. Additionally an operation at high temperatures has to be maintained for a defined time period as the tests of the sensor device should show its durability. In order to reduce the testing effort the applied temperature and the rotation speed have been increased above the parameters for normal operation conditions. The heating unit and the isolated chamber for the rotor with the mounted sensor device are designed to keep the high temperature during the test operation period. Various signals are measured and evaluated during the test period like acceleration at the bearings, rotation speed, temperature. If the sensor device is mounted into a motor, it has to work properly for the whole life cycle of the motor as it cannot be disassembled. Based on a positive test result the long life time of the sensor is demonstrated, which is very important for the reliability and hence the application of the sensor in motors.